Role of Limestone Addition in Improving the Initial Compressive Strength of Geopolymer Concrete for Corrosive Environment Repair - Cahyani, Arwinda Aribah; Husin, Nur Ahmad; Bayuaji, Ridho; Tajunnisa, Yuyun (IPTEK The Journal of Engineering, 2024)
Geopolymer Concrete (GC) is highly durable in corrosive environments, making it a viable material for repair. However, its initial compressive strength was below the 7 MPa required at 1-day age. Adding fine limestone (45 μm) can improve GC's density and early strength. This study explores the effects of adding 0, 3, 5, and 7% limestone and 1% sucrose superplasticizer to GC 16M. The compressive strength was tested at 1, 3, 7, and 28 days, along with slump, permeability, and resistivity tests to assess the durability. The results show that adding 5% limestone yields the optimal GC performance for repairing corrosive environments. The compressive strengths were 15.96, 28, 43, and 67.14 MPa at 3 days, 43 MPa at 7 days, and 67.14 MPa at 28 days, with a slump of 120 mm. The permeability and resistivity results were 0.128 E-16 m² and 57.87 kΩ-cm, indicating normal corrosion levels. These findings confirm that GC with 5% limestone meets the durability and strength requirements of repair materials in corrosive environments.